Transient Receptor Potential Channel 6 Knockout Ameliorates Kidney Fibrosis by Inhibition of Epithelial–Mesenchymal Transition - Zhang, Yanhong; Yin, Nina; Sun, Anbang; Wu, Qifang; Hu, Wenzhu; Hou, Xin; Zeng, Xixi; Zhu, Min; Liao, Yanhong (Frontiers in Cell and Developmental Biology, 2021)
Kidney fibrosis is generally confirmed to have a significant role in chronic kidney disease, resulting in end-stage kidney failure. Epithelial–mesenchymal transition (EMT) is an important molecular mechanism contributing to fibrosis. Tubular epithelial cells (TEC), the major component of kidney parenchyma, are vulnerable to different types of injuries and are a significant source of myofibroblast by EMT. Furthermore, TRPC6 knockout plays an anti-fibrotic role in ameliorating kidney damage. However, the relationship between TRPC6 and EMT is unknown. In this study, TRPC6−/− and wild-type (WT) mice were subjected to a unilateral ureteric obstruction (UUO) operation. Primary TEC were treated with TGF-β1. Western blot and immunofluorescence data showed that fibrotic injuries alleviated with the inhibition of EMT in TRPC6−/− mice compared to WT mice. The activation of AKT-mTOR and ERK1/2 pathways was down-regulated in the TRPC6−/− mice, while the loss of Na+/K+-ATPase and APQ1 was partially recovered. We conclude that TRPC6 knockout may ameliorate kidney fibrosis by inhibition of EMT through down-regulating the AKT-mTOR and ERK1/2 pathways. This could contribute to the development of effective therapeutic strategies on chronic kidney diseases.